Erysipelas-like presentation of Wells’ syndrome (eosinophilic cellulitis) - N. Belfeki; E. Gharbi; C. Flateau; S. Diamantis (Reumatismo, 2020)
Wells’ syndrome, also called eosinophilic cellulitis, is a rare eosinophilic dermatosis characterized by an unspecific inflammatory erythematous eruption often associated with systemic symptoms. Here we report the case of a 57-year-old female with bilateral painful pitting and pruritic feet progressive for two weeks despite one week of oral antibiotics. Skin biopsy was performed showing dermal eosinophilic infiltration. The patient showed a spontaneous progressive improvement of the condition. The presented case demonstrates both clinical and histologic presence of lesions of Wells’ syndrome in the course of the disease. A careful diagnostic approach is needed because of the lack of specific signs. The global outcome is favorable and spontaneous resolution is possible.